Foot Burns in Persons With Diabetes: Outcomes From the National Trauma Data Bank. Issue 3 (17th May 2022) - Perrault, David; Cobert, Jason; Gadiraju, Veda; Sharma, Ayushi; Gurtner, Geoffrey; Pham, Tam; Sheckter, Clifford C
Abstract: Diabetes mellitus (DM) complicates the treatment of burn injuries. Foot burns in diabetic patients are challenging problems with unfavorable outcomes. National-scale evaluations are needed, especially with regard to limb salvage. We aim to characterize lower-extremity burns in persons with DM and evaluate the likelihood of amputation. The National Trauma Data Bank (NTDB) was queried from 2007 to 2015 extracting encounters with primary burn injuries of the feet using International Classification of Diseases (ICD) 9th edition codes. Logistic regression modeled predictors of lower-extremity amputation. Covariables included age, sex, race/ethnicity, comorbidities including DM, % burn TBSA, mechanism, and region of burn center. Poisson regression evaluated temporal incidence rate changes in DM foot burns. Of 116, 796 adult burn encounters, 7963 (7%) had foot burns. Of this group, 1308 (16%) had DM. 5.6% of encounters with DM foot burns underwent amputation compared to 1.5% of non-DM encounters ( P < .001). Independent predictors of lower-extremity amputation included DM (odds ratio 3.70, 95% confidence interval 2.98–4.59), alcohol use, smoking, chronic kidney disease, and burn size >20%, African-American/black race, male sex, and age >40 years (all P < .01). The incidence of DM foot burns increased over the study period with an incidence rate ratio of 1.07 (95% confidence interval 1.05–1.10, P < .001). In conclusion, DM was associated with nearly a 4-fold increase in amputation after adjusting for covariables. Furthermore, the incidence of DM foot burns is increasing. Strategies for optimizing care in persons with DM foot burns are need to improve limb salvage.